The judicialisation of war? Notes on the United Kingdom Supreme Court’s decision in Smith and others v. the Ministry of Defence, and its application of the Human Rights Act 1998 - Ibáñez León, Arturo (Derecho Público Iberoamericano, 2014)
In English law HRA is significantly important because of both its enactment and its practical application. By its enactment, the HRA gave effect in English domestic law to a number of rights enshrined in the European Convention on Human Rights 1950. Furthermore, its practical application has had a fundamental impact on the structure and working of the English legal system. This article’s goal is to consider the latter point of view. To this end, one of the most important decisions on this issue is analysed: the United Kingdom Supreme Court’s decision in Smith and others v. The Ministry of Defence.